To Guide or Not to Guide? Causes and Consequences of Stopping Quarterly Earnings Guidance* - HOUSTON, JOEL F.; LEV, BARUCH; TUCKER, JENNIFER WU (Contemporary Accounting Research, 2010)
In recent years, quarterly earnings guidance has been harshly criticized for inducing managerial short-termism and other ills. Managers are, therefore, urged by influential institutions to cease guidance. We examine empirically the causes of such guidance cessation and find that poor operating performance¿decreased earnings, missing analyst forecasts, and lower anticipated profitability¿is the major reason firms stop quarterly guidance. After guidance cessation, we do not find an appreciable increase in long-term investment once managers free themselves from investors' myopia. Contrary to the claim that firms would provide more alternative, forward-looking disclosures in lieu of the guidance, we find that such disclosures are curtailed. We also find a deterioration in the information environment of guidance stoppers in the form of increased analyst forecast errors and forecast dispersion and a decrease in analyst coverage. Taken together, our evidence indicates that guidance stoppers are primarily troubled firms and stopping guidance does not benefit either the stoppers or their investors.